The urban bioeconomy: extracting value from the ecological and biophysical. Issue 2 (28th January 2021) - Taylor Buck, Nick; While, Aidan
Abstract : Cities have tended to be seen as net consumers of ecological goods and exporters of ecological bads. However, over recent years urban metabolism, circular economy and bioeconomy concepts have sought to rebalance this seemingly parasitical relationship by seeing the urban as an ecological resource to be exploited for profit. In this review paper, we investigate the ways in which the assets and metabolic flows of the city are being recharacterised as a source of value to be maintained, extracted, enhanced and exploited. Our approach is twofold. First, we examine areas of latent potential for urban bioeconomic exploitation and issues raised in terms of fair and just cities. Second, we examine issues, tensions and challenges in reimagining the city as a site of bioeconomic value. The paper makes a distinctive contribution to the literature by defining and critically analysing the new urban bioeconomy as a form of environmental value creation.